2019
DOI: 10.3389/fsufs.2019.00069
|View full text |Cite
|
Sign up to set email alerts
|

How Normal Meat Becomes Stranger as Cultured Meat Becomes More Normal; Ambivalence and Ambiguity Below the Surface of Behavior

Abstract: Although most people still behave like happy meat eaters, there are good reasons to think that many are in fact ambivalent about meat. Following up on earlier findings, in this paper we describe how, in focus groups, cultured meat triggered much discussion about meat, especially among older people. While young people wondered whether they would eat cultured meat products, older people thought about diet changes in a historical perspective and wondered if and how cultured meat might become a societal success. B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 45 publications
(26 citation statements)
references
References 32 publications
0
26
0
Order By: Relevance
“…Previous research has indicated that cultured meat would likely be more appealing to younger people than older people [12,39,41], and new data appears to confirm this [15,28,31,33,35]. Van der Weele and Driessen [37] observed that older people tended to think about cultured meat in terms of the implied societal transition, whereas younger people tended to think about it in terms of their own consumption.…”
Section: Demographic Predictorsmentioning
confidence: 87%
See 4 more Smart Citations
“…Previous research has indicated that cultured meat would likely be more appealing to younger people than older people [12,39,41], and new data appears to confirm this [15,28,31,33,35]. Van der Weele and Driessen [37] observed that older people tended to think about cultured meat in terms of the implied societal transition, whereas younger people tended to think about it in terms of their own consumption.…”
Section: Demographic Predictorsmentioning
confidence: 87%
“…The relative salience of societal vs. personal perspectives may differ for different people. In Dutch focus groups, Van der Weele and Driessen [37] report that younger participants tended to prioritize whether and how they would interact with cultured meat personally, whereas older participants tended to be more reflective on what a societal transition towards cultured meat might look like. Likewise, Bryant et al [21] found that different attitudes were associated with cultured meat acceptance in different countries-while disgust predicted rejection in the US, a positive ethical evaluation predicted acceptance in India.…”
Section: Personal and Societal Considerationsmentioning
confidence: 99%
See 3 more Smart Citations